THE ANALYSIS OF FACTORS AFFECTING THE DEVELOPMENT OF EQUITY FINANCING OF TRUSTEES BPRS AMANAH UMMAH BOGOR (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2017)
Equity financing is a type of financing that is the core business in the Islamic financial institutions and a differentiator with conventional financial institutions. But until now, the total equity financing is still relatively low compared with other types of financing BPRS channeled. BPRS Amanah Ummah is one of the institution conducts equity financing. This study aimed to analyze the influence of sharing profit, DPK, CAR, FDR, inflation, and the BI rate to equity financing at BPRS Amanah Ummah. This study uses Error Correction Model (ECM). The results showed DPK and FDR variables significantly influence the development of equity financing in the short term while variable DPK, CAR, FDR, and the BI rate significantly influence the development of equity financing in the long term however, Profit sharing rate and inflation variable does not significantly influence the development of equity financing.